Calculation of View Factors in Electric Arc Furnace Process Modeling. Issue 2 (7th August 2020) - Hay, Thomas; Hernandez, Jesus; Roberts, Suzanne; Echterhof, Thomas
Abstract : The determination of view factors (VF) is a central component of the heat transfer model in comprehensive electric arc furnace process models. Due to the complex nature of the process, simplifying assumptions are necessary to allow the efficient estimation of VF. These simplifications mainly deal with the geometrical representation of the furnace and the methods to calculate the resulting VF. Such assumptions have been applied in several studies; however, while the results of the complete process models have been validated extensively, the calculated VF have not been examined in detail. Herein, two methods of calculating VF based on a geometry similar to that used in the process models proposed by MacRosty et al., Logar et al., and Meier et al. are presented and validated by comparing the results obtained using a commercial computational fluid dynamics software. The number of assumptions and simplifications is reduced when compared with previously published results and both methods are proven to be accurate while remaining computationally efficient enough for the application in process models for online applications and process optimization, where fast execution is necessary. Abstract : The speed requirement for electric arc furnace (EAF) process models in online and optimization applications necessitates approximate view factor calculations for heat transfer calculations. The accuracy and speed of both a Monte Carlo and an analytical view factor approximation approach are compared. Approximation errors are quantified through comparison with results obtained using the surface‐to‐surface radiation model in Ansys Fluent.